2015
DOI: 10.1007/s10803-015-2363-3
|View full text |Cite
|
Sign up to set email alerts
|

The Understanding of Intentions, Desires and Beliefs in Young Children with Autism Spectrum Disorder

Abstract: This study provides a comprehensive picture of three core elements (Intentions, Desires, Beliefs) of Theory of Mind (ToM) in young children with autism spectrum disorder (ASD, n = 63, Mage = 55 months) and typically developing children (TD, n = 69, Mage = 54 months). Outcomes showed that ASD and TD children understood intentional actions equally well. Yet, children with ASD lacked the social interest to share intentions. Additionally, children with ASD had more difficulties in understanding others’ desires and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 48 publications
0
33
0
3
Order By: Relevance
“…For example, the use of video recording facilitated a shared attention simulation in which the interventionist and the student with autism were both viewing the same events in which the student had participated; thus, the events were not novel and were easy for the student with autism to relate to. Moreover, because of the interactive nature and constant reference to the events in the video recording, this intervention is expected to promote students' declarative comprehension or their ability to make a triadic mental representation (Broekhof et al, 2015;Kristen, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the use of video recording facilitated a shared attention simulation in which the interventionist and the student with autism were both viewing the same events in which the student had participated; thus, the events were not novel and were easy for the student with autism to relate to. Moreover, because of the interactive nature and constant reference to the events in the video recording, this intervention is expected to promote students' declarative comprehension or their ability to make a triadic mental representation (Broekhof et al, 2015;Kristen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Let's check and see if he will do it right this time." It is worth mentioning that each training activity in intervention C was selected according to the individual student's interest; hence, avoiding conflicts in desire among participants (Broekhof et al, 2015). For example, if a student liked cutting and pasting, the intervention was tailored around it.…”
Section: Procedures and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, there is evidence to suggest that the deficits in false belief reasoning may be motivational rather than abilitybased (Begeer, Rieffe, Terwogt, & Stockmann, 2003). In addition, deficits are not uniform across all areas of social-cognitive reasoning; specifically, young children with ASD may not have deficits in understanding intentions (Broekhof et al, 2015) or reading emotions from body postures (Peterson, Slaughter, & Brownell, 2015). The specificity of ToM deficits in children with ASD in turn has informed social-cognitive research and theory because it suggested that understanding psychological causes of behavior may involve specific brain networks.…”
Section: Practical Applicationsmentioning
confidence: 99%